The complex relationship between iron status and anemia in pregnant and postpartum women in India: analysis of two Indian study cohorts of uncomplicated pregnancies - Nair, M; Choudhury, SS; Rani, A; Solomi V, C; Kakoty, SD; Medhi, R; Rao, S; Mahanta, P; Zahir, F; Roy, I; Chhabra, S; Deka, G; et al. (Wiley, 2023)
Low hemoglobin is widely used as an indicator of iron deficiency anemia in India and other low-and-middle income counties, but anemia need not accurately reflect iron deficiency. We examined the relationship between hemoglobin and biomarkers of iron status in antenatal and postnatal period. Secondary analysis of uncomplicated singleton pregnancies in two Indian study cohorts: 1132 antenatal women in third trimester and 837 postnatal women 12–72 h after childbirth. Associations of hemoglobin with ferritin in both data sets, and with sTfR, TSAT, and hepcidin in the postnatal cohort were examined using multivariable linear regression. Multinomial logistic regression was used to examine the association between severity of anemia and iron status. Regression models were adjusted for potential confounders. Over 55% of the women were anemic; 34% of antenatal and 40% of postnatal women had low ferritin, but 4% antenatal and 6% postnatal women had high ferritin. No evidence of association between hemoglobin and ferritin was observed (antenatal: adjusted coefficient [aCoef] −0.0004, 95% confidence interval [CI] −0.001, 0.001; postnatal: aCoef −0.0001, 95% CI −0.001, 0.001). We found a significant linear association of hemoglobin with sTfR (aCoef −0.04, 95% CI −0.07, −0.01), TSAT (aCoef −0.005, 95% CI −0.008, −0.002), and hepcidin (aCoef 0.02, 95% CI 0.02, 0.03) in postnatal women. Likelihood of low ferritin was more common in anemic than non-anemic women, but high ferritin was also more common in women with severe anemia in both cohorts. Causes of anemia in pregnant and postpartum women in India are multifactorial; low hemoglobin alone is not be a useful marker of iron deficiency.